Reconciliation Through Education: A Model of Ethical Spaces and Relationality - Poitras Pratt, Yvonne; Bodnaresko, Sulyn (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2023)
As more alarming truths are being revealed around the horrors of the residential schooling system in Canada, educators are being called to decolonize and Indigenize their teaching practices. As post-secondary teacher educators working in Indigenous education who have gained valuable insights around this difficult teaching, the authors offer readers a conceptual model of reconciliatory education. The model invites educators to move beyond colonial schooling practices to embrace decolonizing and Indigenizing approaches and the powerful potential of relational teaching and learning. Envisioned as an ethical space residing between Indigenizing and decolonizing practices and animated by truth-telling and critical thinking, the extended infinity model, presented in this article, shows the dynamic nature of teaching and learning that occurs when relating together through commitments to decolonizing and Indigenizing. While purposefully engaging in an ethos of ethical relationality, the model carries transformative potential for teaching and learning.